2022
DOI: 10.1039/d2ra04037a
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution, photoelectron spectra and vibrational properties of anionic GdGen (n = 5–18) nanoalloy clusters: a DFT insight

Abstract: The structural evolution, electronic and vibrational properties of GdGen− (n=5-18) nanoclusters were studied by quantum chemical calculations, which revealed GdGe16− nanocluster is a superatom to the orbital of 1S21P6(4f7)1D101F142S22P21G182P42D10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For n = 10, similar to the YSi 10 – cluster, the GM configuration is the linked structure ( 10A1 ) of the 1 A ground state in which the Y atom links two orthogonal Ge 5 trigonal bipyramids. The 10A2 isomer, similar to 10c geometry in ref , is also a linked structure. 10A3 is a linked configuration, in which the Y atom connects a Ge 4 subcluster and a capped trigonal bipyramid.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…For n = 10, similar to the YSi 10 – cluster, the GM configuration is the linked structure ( 10A1 ) of the 1 A ground state in which the Y atom links two orthogonal Ge 5 trigonal bipyramids. The 10A2 isomer, similar to 10c geometry in ref , is also a linked structure. 10A3 is a linked configuration, in which the Y atom connects a Ge 4 subcluster and a capped trigonal bipyramid.…”
Section: Resultsmentioning
confidence: 60%
“…Recently, Yang et al ,, studied the structural evolution and electronic properties of introducing a Lu atom into Ge n ( n = 5–17) compounds in neutral, anionic, and cationic states and found that the ultraviolet–visible (UV–vis) spectra of LuGe 16 – and LuGe 17 + clusters match with solar energy distribution, which make them the most suitable building blocks for potentially usage in solar energy converters or ultrahigh-sensitive near-infrared photodetectors. More recently, the spatial structure and electron energy spectra of Gd-doped anionic Ge n – clusters have been reported . Here, a global search algorithm and a double-hybrid density functional were applied for geometric optimization for introducing Y into Ge anionic clusters (YGe n – ( n = 6–20)) with the purpose of combing their global minimum (GM) structure features and evolutions, simulating their PES, infrared, Raman, and specific-sized ultraviolet–visible (UV–vis) spectra and comparing simulated PES spectra with previous experimental ones .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “substitution geometries” was the second approach, used to replace one Sn atom in the Sn n +1 compound with the Zr atom. The third approach that was executed selects the configurations that have already been published in the previous literature as supplements. , For the second phase, these initial isomers were then further optimized at PBE0, B3LYP, , and CAM-B3LYP functionals, respectively, which provided reliable results. Considering the high computational costs and accuracy, we chose the triple-ζ LANL2TZ , basis set for the Zr atom, which is provided with a quasi-relativistic effective core potential, and the cc-pVTZ-PP , basis set for the Sn atom, which is provided with a relativistic effective core pseudopotential. Symmetry constraints were not presented during this process.…”
Section: Methodsmentioning
confidence: 99%
“…Since the discovery of the buckminster fullerene C 60 structure of the carbon group, the unique geometries, analogous and diverse physicochemical and structural properties of the heavy congeners of carbon Si, Ge, Sn, and Pb, as well as their wide range of applications in nanotechnology and electronics industries have resulted in their being surprisingly hot spots for nanoscale research in cluster science. Especially, the stannum element shows the α-phase (gray diamond cubic structure having a covalent nature) and β-phase (white body-centered tetragonal structure with a metallic nature), existing as a transition from semiconductor to metal in the carbon group. These unique characteristics of the transition endow the stannum element with a low melting point, nontoxicity, high corrosion resistance, good ductility, and wettability, leading to its wide application in industries such as electronics, electrical appliances, metallurgy, machinery, building materials, chemical engineering, and others.…”
Section: Introductionmentioning
confidence: 99%